Determination of Performance Analysis for an Underground Colliery Utilizing Mechanized Production System: Determination of Performance Analysis for an Underground Colliery Utilizing Mechanized Production System - Arıtan, Ali Ekrem; Şensöğüt, Cem (International Journal of Economic and Environmental Geology, 2019)
Performance is one of the most important parameters for today’s business organizations. An organization that is low on performance, no matter how much high quality products they have, cannot take the share they desire from the market. It is the inevitable result for organizations with low performances to lose money and get closed down. Nowadays performance is measured in many ways. In this work; the production performance of Ömerler Colliery, which is the only government controlled mechanized lignite mine authorized under the Western Lignite Corporation (WLC) and the factors that caused performance decrease has been determined. In order to gain performance measurements; effectiveness, efficiency and productivity criteria have been used and performance indexes have been acquired. As the result of the performance analysis, it is understood that there has been malfunctions with; in order; belt conveyor, chain conveyor, shearer and fortification that has been effective in the decrease of performance. Performance indexes, which are barely derived from the multiplication of performance parameters, are examined and it is deducted that the highest relation is achieved for the efficiency parameter with a correlation constant (r) of 0.9489 and a certainty constant (R²) of 0.9005 while the lowest relation is obtained for the efficiency parameter with a correlation constant (r) of 0.4621 and certainty constant (R²) 0.2135. With this acquired result it has been determined that by only measuring effectiveness, performance detection cannot be made.